Electronic portfolios and learner identity: an ePortfolio case study in music and writing - Bennett, Dawn; Rowley, J.; Dunbar-Hall, P.; Hitchcock, M.; Blom, D. (2014)
Although the employability of graduates is of concern across further and higher education it is particularly problematic in the arts disciplines, from which few students transition to a traditional, full-time position. Arts graduates shape their work to meet personal and professional needs, and the successful negotiation of this type of career requires a strong sense of identity and an awareness of diverse opportunities. The challenge for educators is how we might develop these capacities whilst being mindful of students' dreams, which are often focused on artistic excellence and recognition. This paper reports findings from a collaborative study undertaken at four Australian universities. With a focus on developing an electronic portfolio (eP), the study involved students in classical and contemporary music, music education, music technology, creative writing and professional writing. The combination of music and writing provided points of comparison to identify issues specific to music, and those that might apply more generally. This paper reports findings related to learner identity, drawing evidence from survey and interview data. The study, which was driven by the learning process rather than the technological tool, revealed that students' use of eP transitions from archive to self-portrait. Moreover, the eP emerged as a vehicle through which identity is negotiated and constructed. Indeed, the process of developing of an eP prompted students to adopt future-oriented thinking as they began to redefine their learning in relation to their future lives and careers. These findings were common to all students, regardless of discipline or technological platform. © 2014 © 2014 UCU.